Legal Policy of Constitutional Complaints in Judicial Review: A Comparison of Germany, Austria, Hungary, and Indonesia - Lailam, Tanto; Andrianti, Nita (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2023)
This article focuses on the legal policy of constitutional complaints in judicial review. It compares the European model (Germany, Austria, Hungary) and Indonesia. These four countries have a legal policy in common, a constitutional court with a centralised court system and judicial review (abstract judicial review, concrete judicial review, and constitutional complaints), but the MKRI lack constitutional complaint. Three constitutional complaints policies in these courts can be used as a reference for the strengths and weaknesses of each judiciary on regulations and legal practices. However, Germany's constitutional complaints policy is better than Austria's and Hungary's. Its excellence is caused all ordinary court decisions as an object dispute; decisions are final and binding; individuals and organisations can submit this application and legal aid by the lawyers or professor of law in the oral hearing; the process only takes one month and is free of charge and the trial with or without an oral hearing. In the future, MKRI needs this authority with legal policy steps amending the MKRI Act, and the last step is an amendment to the 1945 Constitution.